Compassionate Communities: Community intervention for the prevention of complicated grief. Model implemented by Madrid Salud - Carrascosa Pujalte, Elisa; Valero Herranz, Elena; Adán Pérez, Esther; Garrido Sanz, Virginia; Trujillo Mejía, Ximena; Plaza Bedmar, Gonzalo; Casla Puig, Ana; Adame Ortíz, Ana; Lorenzo González, Rosalía (Psicooncología, 2023)
Objective: The main objective of the Compassionate Communities project in the city of Madrid is to strengthen people’s ability to face and accompany grief situations through a community perspective. Methodology: Design of two intervention axes: sensitization and training of the population and professionals, and development of group spaces aimed at preventing complicated grief. Result: A diagnosis of the city of Madrid has been carried out. Sixty trainings have been carried out for Madrid Salud staff and 32 for professionals and community organizations. There have been 327 sensitizations about the end of life and bereavement (5,873 people). Contact was established with 283 public resources and 158 private resources throughout the year. Finally, a total of 15 Group Spaces for Grieving Support have been carried out. Conclusions: The compassionate communities model of the city of Madrid has managed to strengthen the capacities of the citizens of Madrid for collective care through the different awareness-raising activities and to impact on the professional strengthening and sensitivity of health professionals in relation to the key concepts of the project, thus generating a compassionate community.
Keywords: Madrid Salud; Compassionate communities; grief; end of life; health promotion